Treatment-related mortality in head and neck cancer patients receiving chemotherapy and radiation: results of a meta-analysis of published trials - Cristina Gurizzan; Michela Cinquini; Lorenzo Legramandi; Carlo Resteghini; Marco Siano; Cristiana Bergamini; Luigi Lorini; Davide Smussi; Alberto Paderno; Lisa Licitra; Paolo Bossi (Therapeutic Advances in Medical Oncology)
Objectives: A combination of chemotherapy and radiotherapy is employed in the curative and postoperative treatment of locally advanced head and neck cancers (HNC). Integrated chemoradiation (CRT) treatments result in a non-negligible rate of severe toxic effects. Treatment-related death (TRD) is a crucial topic for physicians involved in the curative treatment of HNC. This meta-analysis aimed to better address TRD in locally advanced HNC patients treated with CRT through available and relevant literature. Methods: We performed a systematic review of the literature according to the PRISMA statement. The studies fulfilling these criteria included the following: concurrent or alternating CRT; both radical and postoperative settings; published from 2000 to 2020; involving 100+ patients; and available toxicity data. TRD was defined as death occurring from CRT start until a month from the end of CRT. Potential TRD predictors were evaluated. Results: In all, 65 studies were retrieved, with a total of 235 TRDs reported accounting for an overall risk rate of 1.4%. At meta-regression analysis, T stage and neutropenia grade >3 were potential predictors of higher TRD risk, both in univariate and multivariate analyses. Considering only the studies reporting at least one event, laryngeal/hypopharyngeal, oral cavity subsites and renal failure were significant predictors for TRD. The oropharyngeal subsite was protective in both analyses. None of the predictors proved to be independently correlated with TRD at multivariable analysis. Conclusion: CRT in HNC resulted in 1.4% of TRDs. TRD rate reduction may imply better patient selection and more intensive supportive care programs.